Housing in times of crisis – effects of the Covid-19 pandemic and the energy crisis on housing preferences and housing location decisions - Münter, Angelika; Garde, Lisa; in der Beck, Lea; Osterhage, Frank (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
Since the beginning of this decade, society has been confronted with multiple crises that also act as new drivers of spatial development. Based on a literature review and qualitative interviews with housing market actors, this paper presents an interim balance of the lasting influence of the Covid-19 pandemic on housing preferences and location decisions as well as initial empirical knowledge and theses on the effects of the 2022 energy crisis on these decisions. It emerges that the energy crisis already has a greater impact on spatial development today and will probably have a greater impact in the medium and long term than the pandemic. Housing preferences that arose during the pandemic have already shifted again or can no longer be implemented at present. At the same time, the influences of the pandemic can no longer be considered in isolation from the energy crisis. While the pandemic will further intensify spatial deconcentration processes, the effects of the energy crisis are spatially more differentiated. Moreover, in a time of multiple crises, future spatial development will not be shaped by individual crises, but by their interaction – also with long-standing trends such as the ageing of society.